The Dynamics of Santri Identity in the Digital Era: A Psychosocial Analysis of the Influence of Virtual Toxicity on the Identity Crisis among Alumni of Islamic Boarding Schools - Ilmiyah, Nahdliyatul; Hanum, Najwa Adibah; Zuhrin, Auliya; Afwadzi, Benny (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2026)
In the current digital era, university students who are alumni of Islamic boarding schools are increasingly vulnerable to exposure to toxic online environments, including harmful interactions, online disinhibition, cyberbullying, FoMO (Fear of Missing Out), and the pursuit of social validation. These factors have the potential to trigger identity crises and significantly disrupt their psychosocial stability. This study aims to examine comprehensively and in depth the dynamics of self-identity among Islamic boarding school alumni amid exposure to a digitally toxic environment. This research employs a mixed-methods approach with a sequential explanatory design, involving quantitative data collection through questionnaires administered to 130 alumni of Islamic boarding schools currently studying at universities in Malang City. This is followed by in-depth interviews and observations of six qualitative informants to further elaborate on the findings. The results indicate a positive and significant influence of virtual toxicity on identity crises, with a coefficient of determination (R²) of 0.135, or 13.5%. This suggests that virtual toxicity accounts for 13.5% of the variance in identity crises, while the remaining percentage is influenced by other factors, such as social and family environments. From a psychosocial perspective, exposure to toxic virtual environments has been shown to weaken commitment to traditional santri values, create role confusion, and shift students’ self-orientation away from the religious principles they uphold. This study highlights the importance of strengthening digital literacy and providing character guidance grounded in the values of Islamic boarding schools to ensure that the santri identity remains resilient amid the rapid flow of the virtual world.